Extraction and clean-up procedure for analysis of organochlorine pesticide residues in ethoxylated lanolin - Polese, L.; Sannomiya, M.; Sader, APD; Ribeiro, M. L. (Elsevier B.V., 2000)
In the present study an evaluation was made of a method for the determination of organochlorine pesticide residues in ethoxylated lanolin. Samples were homogenized with Celite, transferred to chromatographic columns, prepacked with silica gel deactivated to 10%. The pesticide elution was processed with n-hexane-dichloromethane and the concentrated eluate was analyzed using gas-liquid chromatography (GC) with electron capture detection (ECD). The composition of the elution solvent was a significant factor for the recovery of the pesticides. Mean recoveries obtained for fortified samples ranged from 87 to 94% for p,p'-DDE, dieldrin, endrin, p,p'-DDD and p,p'-DDT. Optimization of the experimental conditions resulted in a small-scale method that combines extraction and cleanup in a single step. (C) 2000 Elsevier B.V. S.A. All rights reserved.
Keywords: organochlorine pesticides; ethoxylated lanolin; gas chromatography